Haplets: Finger-Worn Wireless and Low-Encumbrance Vibrotactile Haptic Feedback for Virtual and Augmented Reality - Preechayasomboon, Pornthep; Rombokas, Eric (Frontiers in Virtual Reality, 2021)
We introduce Haplets, a wearable, low-encumbrance, finger-worn, wireless haptic device that provides vibrotactile feedback for hand tracking applications in virtual and augmented reality. Haplets are small enough to fit on the back of the fingers and fingernails while leaving the fingertips free for interacting with real-world objects. Through robust physically-simulated hands and low-latency wireless communication, Haplets can render haptic feedback in the form of impacts and textures, and supplements the experience with pseudo-haptic illusions. When used in conjunction with handheld tools, such as a pen, Haplets provide haptic feedback for otherwise passive tools in VR, such as for emulating friction and pressure-sensitivity. We present the design and engineering for the hardware for Haplets, as well as the software framework for haptic rendering. As an example use case, we present a user study in which Haplets are used to improve the line width accuracy of a pressure-sensitive pen in a virtual reality drawing task. We also demonstrate Haplets used during manipulation of objects and during a painting and sculpting scenario in virtual reality. Haplets, at the very least, can be used as a prototyping platform for haptic feedback in virtual reality.